2016
DOI: 10.1158/1541-7786.mcr-15-0479
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Causes Cell Cycle Arrest in LKB1-Deficient Cells via Activation of CAMKK2

Abstract: The AMP-activated protein kinase (AMPK) is activated by phosphorylation at Thr172, either by the tumor suppressor kinase LKB1 or by an alternate pathway involving the Ca 2þ /calmodulindependent kinase, CAMKK2. Increases in AMP:ATP and ADP:ATP ratios, signifying energy deficit, promote allosteric activation and net Thr172 phosphorylation mediated by LKB1, so that the LKB1-AMPK pathway acts as an energy sensor. Many tumor cells carry loss-of-function mutations in the STK11 gene encoding LKB1, but LKB1 reexpressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 51 publications
3
46
0
Order By: Relevance
“…7D). We have shown previously that A23187 treatment of G361 cells causes a G 1 arrest that is abolished in AMPK DKO cells (22). Supplementary Figure S4 confirms that, similar to HeLa cells, prior treatment with A23187 protected G361 cells against cell death induced by etoposide in clonogenic survival assays, with the effect being abolished in DKO cells.…”
Section: A23187 Enhances Cell Survival During Etoposide Treatment Viasupporting
confidence: 75%
See 2 more Smart Citations
“…7D). We have shown previously that A23187 treatment of G361 cells causes a G 1 arrest that is abolished in AMPK DKO cells (22). Supplementary Figure S4 confirms that, similar to HeLa cells, prior treatment with A23187 protected G361 cells against cell death induced by etoposide in clonogenic survival assays, with the effect being abolished in DKO cells.…”
Section: A23187 Enhances Cell Survival During Etoposide Treatment Viasupporting
confidence: 75%
“…AMPK activation using the pharmacologic activator 5-aminoimidazole-4-carboxamide ribonucleoside (46), or by glucose deprivation or overexpression of a mutant (T172D) AMPK kinase domain (47), causes cell-cycle arrest in G 1 phase. We have recently confirmed that these effects of AMPK activators, which are associated with increased expression of the cyclin-dependent kinase inhibitor p21 (CDKN1A), are AMPK dependent as they were abolished by a double knockout of AMPK (22). A cell-cycle arrest in G 1 phase would limit the entry of cells into S-phase, where they are particularly vulnerable to the generation of double-stranded DNA breaks induced by etoposide while DNA is being replicated.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, the HeLa cell line is severely impaired in LKB1 activity (30). The present study showed that inducible expression of MARK2 in HeLa cells was sufficient to mimic LKB1 signaling activation as previously reported (12)(13)(14), and further confirms that MARK2 is a critical downstream target of LKB1.…”
Section: Discussionsupporting
confidence: 90%
“…When cellular AMP:ATP ratios rise, LKB1 directly phosphorylates the threonine 172 (Thr172) in the activation loop of AMPK and results in an increase in ATP-producing activities and a decrease in ATP-consuming processes including essentially all biosynthetic pathways required for cell growth (10,11). Previous investigations have shown that activation of the LKB1-AMPK pathway is able to suppress cell growth by arresting the cell cycle in the G1 phase (12,13). In a similar manner, we confirmed and extended these observations by demonstrating that exogenous activation of LKB1-AMPK signaling induces downregulation of cyclins (cyclin D1 and D3) and upregulation of the cyclin-dependent kinase (CDK) inhibitors (p53, p21 and p16), and thus, inhibits G1/S cell cycle transition, even in cells with endogenous expression of LKB1 (14).…”
Section: Introductionmentioning
confidence: 99%